If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -1n = 0 Solving 13 + -1n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -1n = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -1n = 0 + -13 -1n = 0 + -13 Combine like terms: 0 + -13 = -13 -1n = -13 Divide each side by '-1'. n = 13 Simplifying n = 13
| -13x+2x=-39+12x | | B-380=-236 | | x^6-6x=0 | | 18.7j-15.25=4.5j+6.83+15.4j | | 18.7j-7.8=8.8 | | 3y^2+18y-25=-3 | | -3D-11=33 | | 5q+6=-69 | | Z+32=78 | | v-4/5=15/4 | | 0.25y-y^3= | | W+28=53 | | v-4/5=33/4 | | 19=-7(a-19) | | 2.5x+6y=40 | | Y=ln(sin(5x)) | | U-2=17 | | 4.5z=30 | | 1-(5/6x)=x/6 | | -5(p-19)=-6 | | 2x=0.4+0.8x^2+0.4x^4 | | e+5r+r+9e=72 | | y-4/5=1/3 | | 3.2+0.3=0.2x | | 8+y=b | | 4y+3+8y+7=16 | | (10*x+y)=2((10*y)+(2*x)) | | 4x+2=8x-10 | | Y=(5x^2+4)sin(4x^3) | | ln(8x)=2.9 | | 5x-7x=-3 | | p^2+23p-50= |